2016
DOI: 10.1002/2015wr018509
|View full text |Cite
|
Sign up to set email alerts
|

Extending Theis' solution: Using transient pumping tests to estimate parameters of aquifer heterogeneity

Abstract: A framework for interpreting transient pumping tests in heterogeneous transmissivity fields is developed to infer the overall geostatistical parameters of the medium without reconstructing the specific heterogeneous structure point wise. The methodology of Radial Coarse Graining is applied to deduce an effective radial description of multi-Gaussian transmissivity. It was used to derive an Effective Well Flow Solution for transient flow conditions including not only the storativity, but also the geometric mean,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 39 publications
(56 reference statements)
0
29
0
Order By: Relevance
“…Zech and Attinger () recently showed that for heterogeneous aquifers, steady state estimates of T (using the Theim equation) are biased. Zech and Attinger () and Zech et al () presented pumping drawdown equations for the unbiased estimation of T and drawdown within heterogeneous aquifers and which included parameters for the spatial variance and spatial correlation in T . Synthetic applications show that unbiased local and aquifer average T values can be derived.…”
Section: Discussionmentioning
confidence: 99%
“…Zech and Attinger () recently showed that for heterogeneous aquifers, steady state estimates of T (using the Theim equation) are biased. Zech and Attinger () and Zech et al () presented pumping drawdown equations for the unbiased estimation of T and drawdown within heterogeneous aquifers and which included parameters for the spatial variance and spatial correlation in T . Synthetic applications show that unbiased local and aquifer average T values can be derived.…”
Section: Discussionmentioning
confidence: 99%
“…This latter paper 125 also discusses the quantity and spatial coverage of the data needed to obtain reliable 126 estimates of the statistical parameters of the transmissivity field. Zech et al (2016) extended 127 the analysis to transient flow and showed that the number of measurements needed to obtain 128 reliable estimates of the transmissivity spatial structure is reduced compared to steady state 129 pumping tests. 130…”
Section: Copty and Findikakis (2004a) Examined The Sensitivity Of Tramentioning
confidence: 99%
“…In case of non-fractal media, Gaussian correlation functions of the log-hydraulic conductivity field Y are often used, due to their simple mathematical treatment (Dagan 1988;Gelhar 1993;Dentz et al 2000a;Zech et al 2012Zech et al , 2016. In a d-dimensional isotropic medium they have the form…”
Section: Correlation Function For Isotropic Fractal Mediamentioning
confidence: 99%